Pelaksanaan Workshop Literasi Keuangan Dan Kesiapan Berumah Tangga di Desa Madiredo Kecamatan Pujon - Alif Achadah; Novita Fadia Rahma P; Faizatul Husnah (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Financial literacy includes an understanding of personal financial management, financial future planning, investment, and financial risk management. On the other hand, marriage readiness involves interpersonal skills, financial responsibility, and the ability to face challenges and conflicts in domestic life. The research method used in this research is Survey and Participatory Observation. Surveys were conducted before and after the workshop to measure the level of increase in participants' understanding regarding financial literacy and household readiness. This survey is designed to cover various aspects, including understanding of financial management, planning for the financial future, and knowledge about preparing for a household. Apart from surveys, participatory observation was also carried out during the workshop. This observation aims to understand in depth the interactions between KKN-T Kel 09 students and the Madiredo Pujon Malang Village Community. By directly observing workshop activities, researchers can see how participants respond to the material presented, the extent of their understanding of these topics, and how the interactions between participants and workshop facilitators are. The survey results showed a significant increase in the Madiredo Community's understanding of financial literacy after attending the workshop.